Impact of Adsorbent Weight, Time, and Temperature on Purification Efficiency with Activated Carbon - Rusly Ma'arief; Abdul Haris Mulyadi; Yeti Rusmiati Hasanah (Research in Chemical Engineering, 2024)
Based on data from the Indonesian Biofuel Producers Association 2022, biodiesel production will reach 10.8 billion liters, producing crude glycerol of 10-20% of the total product volume in the transesterification process. Crude Glycerol is a by-product of making biodiesel with low purity because it still contains impurities such as methanol, free fatty acids, KOH catalysts, and water. These impurity compounds must be removed so that the quality of glycerol increases and has a high selling value. Adsorption is one method that can be used to absorb these impurity compounds. This research aims to determine the effect of adsorbent weight, adsorption time, and temperature on glycerol purity levels. This experimental research uses an exploratory factorial design method to determine the most influential factors. The low level of adsorbent weight used is 9%, while the high level of adsorbent weight is 15%. The low-level adsorption time is 60 minutes and the high level is 90 minutes. The adsorption temperature used is a low level of 40℃ and a high level of 80℃. The research results showed that the weight of the adsorbent was the factor that had the most influence on the purity level of glycerol